The detrimental effect of COVID‐19 nationwide quarantine on accelerometer‐assessed physical activity of heart failure patients. (22nd July 2020) - Vetrovsky, Tomas; Frybova, Tereza; Gant, Iulian; Semerad, Miroslav; Cimler, Richard; Bunc, Vaclav; Siranec, Michal; Miklikova, Marie; Vesely, Jiri; Griva, Martin; Precek, Jan; Pelouch, Radek; et al.
Abstract: Aims: A reduction of habitual physical activity due to prolonged COVID‐19 quarantine can have serious consequences for patients with cardiovascular diseases, such as heart failure. This study aimed to explore the effect of COVID‐19 nationwide quarantine on accelerometer‐assessed physical activity of heart failure patients. Methods and results: We analysed the daily number of steps in 26 heart failure patients during a 6‐week period that included 3 weeks immediately preceding the onset of the quarantine and the first 3 weeks of the quarantine. The daily number of steps was assessed using a wrist‐worn accelerometer worn by the patients as part of an ongoing randomized controlled trial. Multilevel modelling was used to explore the effect of the quarantine on the daily step count adjusted for weather conditions. As compared with the 3 weeks before the onset of the quarantine, the step count was significantly lower during each of the first 3 weeks of the quarantine ( P < 0.05). When the daily step count was averaged across the 3 weeks before and during the quarantine, the decrease amounted to 1134 (SE 189) steps per day ( P < 0.001), which translated to a 16.2% decrease. Conclusions: The introduction of the nationwide quarantine due to COVID‐19 had a detrimental effect on the level of habitual physical activity in heart failure patients, leading to an abrupt decrease of daily step count that lasted for at least the 3‐week study period. Staying active and maintaining sufficient levels of physical activity during the COVID‐19 pandemic are essential despite the unfavourable circumstances of quarantine.